Beyond copy number: A new, rapid, and versatile method for sequencing the entire SMN2 gene in SMA patients. Issue 6 (6th April 2021) - Blasco‐Pérez, Laura; Paramonov, Ida; Leno, Jordi; Bernal, Sara; Alias, Laura; Fuentes‐Prior, Pablo; Cuscó, Ivon; Tizzano, Eduardo F.
Abstract: Spinal muscular atrophy (SMA) is caused by bi‐allelic loss or pathogenic variants in the SMN1 gene. SMN2, the highly homologous copy of SMN1, is considered the major phenotypic modifier of the disease. Determination of SMN2 copy number is essential to establish robust genotype–phenotype correlations and predict disease evolution, to stratify patients for clinical trials, as well as to define those eligible for treatment. Discordant genotype–phenotype correlations are not uncommon in SMA, some of which are due to intragenic SMN2 variants that may influence the amount of complete SMN transcripts and, therefore, of full‐length SMN protein. Detection of these variants is crucial to predict SMA phenotypes in the present scenario of therapeutic advances and with the perspective of SMA neonatal screening and early diagnosis to start treatments. Here, we present a novel, affordable, and versatile method for complete sequencing of the SMN2 gene based on long‐range polymerase chain reaction and next‐generation sequencing. The method was validated by analyzing samples from 53 SMA patients who lack SMN1, allowing to characterize paralogous, rare variants, and single‐nucleotide polymorphisms of SMN2 as well as SMN2 – SMN1 hybrid genes. The method identifies partial deletions and can be adapted to determine rare pathogenic variants in patients with at least one SMN1 copy. Abstract : We developed a new affordable and versatile method that, by means of long PCR and NGS, allows sequencing the entire SMN2 genes of spinal muscular atrophy (SMA) patients detecting point variants, copy number variants and hybrid SMN1‐SMN2 genes. This complete characterization of the SMN2 structure in each patient will improve our knowledge of the genotype‐phenotype correlation, the phenotype prediction in the context of newborn screening and pre‐symptomatic diagnosis and also will potentially allow the identification of new phenotype modifier variants.